Digital Outcrop Model reconstructions of diverse geomorphologies based on Zhurong rover data (Utopia Planitia; Mars) - Gwénaël Caravaca; Zhaopeng Chen; Stéphane Le Mouélic; François Civet; Xin Ren; Agnès Cousin; Sylvestre Maurice (Icarus, 2026)

Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Long-term organic fertilization fosters modular microbial networks: A global analysis of soil bacteriome responses - Shu-Le Li; Cai Chen; Xiang-Yu Dai; Hai-Song Yan; Yao-Yang Xu; Meili Feng; Jun He; Jianfeng Ren; Wan-Ying Xie; Fang-Jie Zhao (Soil Ecology Letters, 2026)

Precise H2 supply enables quantitative control of on-demand deep nitrate removal while preserving denitrification completeness - Ge Yan; Zhen-Xiang Jiang; Jia-Le Wu; Ting Wang; Jun-Tong Hu; Li-Wen Qiu; Chen Zhou; Hongqiang Ren (Water Research, 2026)

Multi-scale evolutionary mechanisms of suffusion in gap-graded soil under coupled cyclic hydro-mechanical loading - Hao Xiong; Jiaxin Huang; Mayao Cheng; Xiusong Shi; Zengle Ren; Le Wang; Xiangsheng Chen (Computers and Geotechnics, 2026)

Rational design of bispecific aptamers with high stability and affinity - Shuang Jiang; Yueyang Ren; Xue Wang; Jingwen Xie; Yuzhuo Chen; Yaning Liang; Xianlu Lei; Yong Xie; Tao Le (Analytica Chimica Acta, 2026)

A microalgae-biochar hybrid for synergistic glyphosate removal and phosphorus assimilation: Coupling physical adsorption with biological transformation - Le Fang; Yifan Xing; Cheng Zhang; Guodong Su; Ze Ren; Xia Li (Journal of Environmental Chemical Engineering, 2026)

Balancing N₂O and NH₃ emissions with maize yield: Investigating the role of alternate drip irrigation and 3,4-dimethylpyrazole phosphate (DMPP) - Junming Liu; Yuanyuan Fu; Le Yang; Zhuanyun Si; Sunusi Amin Abubakar; Huijie Li; Tao Zhou; Ruiqi Ren; Hongchen Li; Peng Li; Bingcheng Si; Yang Gao; et al. (Soil and Tillage Research, 2026)

Wet suppression of coal dust by Physical, Chemical, and synergistic Methods: A Review - Le Chen; Guochao Yan; Shaoqi Kong; Kai Ren; Jiawei Zhang; Gang Li (Minerals Engineering, 2026)

A novel AGTPBP1-ERK/MYLK network mediates pancreatic cancer progression - Zhe-yu Yang; Qian Zhang; Jing-rui Yang; Xiao-dong Zhang; Chang-le Liu; Jia-yu Huang; Rui Xiao; Jian-jun Ren (Tissue and Cell, 2026)

Robust source tracing for solid waste via machine learning-enabled mineralogical fingerprinting - Le Lin; Changhai Ren; Shen Qu; Yang Xiao; Yin Li; Xueming Liu; Han Wang; Zhang Lin (Resources, Conservation and Recycling, 2026)

A process-informed multi-parameter downscaling framework for high-resolution source apportionment of riverine nutrients - Xia Li; Chouai Cai; Le Fang; Cheng Zhang; Ying Peng; Qichun Yang; Ze Ren; Xinhui Liu (Journal of Hydrology, 2026)

Development of combined mutagenesis strategy for enhanced eicosapentaenoic acid production in Schizochytrium sp. - Kai-Xin Liu; Qing Chen; Zi-lei Chen; Chun-Yong Jiang; Yang Wu; Xiu-Juan Li; Xiao-Le Liu; Min-Jie Cao; Bo Ren; Ya-Qiong Yang; Dong-Sheng Guo (Bioresource Technology, 2026)

Analysis, isolation and anti-tumour activity of the alkaloids from Ceratocarpus arenarius L - Aimulaguli Kuerban; Hanghang Fu; Yanni Ma; Dongyu Lei; Xingyu Ren; Lu Jin; Le Pan (Natural Product Research, 2026)

A digital-enabled circular recovery system for post-consumer inhalers: Linking material recovery, behaviour, and carbon reduction - Huong Thanh Hoang; Luong Cao Tung Son; Yu-Fen Huang; Ren-Hao Pan; Phuong Truc Nguyen Le; I-Chun Chuang; Huang-Chi Chen; Hung-Pin Tu; Chih-Hsing Hung; Da-Wei Wu (Journal of Cleaner Production, 2026)

Mechanistic insights into glufosinate-ammonium (GLA)-Induced brain injury revealed by LC-MS/MS-based metabolomics - Huan-le Ye; Xin-xin Zheng; Mian-mian Li; Zhi-qiang Zhang; Liu-xu Chen; Wen-jing Zhang; Ren Cheng-Han Fan; Guo-xin He; An-cong Xu (Chemico-Biological Interactions, 2026)

Accurate topside ionospheric TEC estimation using LEO satellites with onboard GPS observations - Xiaodong Ren; Jianfeng Wu; Xuan Le; Yuhang Yang; Haochen Yang; Linghuo Jian; Xiaohong Zhang (GPS Solutions, 2026)

Deciphering the interplay between cuproptosis and mitochondrial energy metabolism in thyroid cancer: a multi-omics study for molecular subtyping, prognosis, and tumor microenvironment characterization - Hongbo Le; Yang Wu; Nan Wu; Ren Jing; Xi Zhou; Yanxing Li; Shijian Yi; Huihong Zhang (Molecular and Cellular Biochemistry, 2026)

Exposure to polycyclic aromatic hydrocarbons during maternal pregnancy: Effects of DNA damage on neural tube defects in offspring - Xiaoqian Jia; Yingfeng Gao; Yuan Li; Ruiwei Xu; Lei Jin; Linlin Wang; Aiguo Ren; Le Zhang; Yali Zhang; Shanshan Lin; Jicheng Gong; Zhiwen Li (Journal of Hazardous Materials, 2026)

Utilizing spirulina immunoactive peptide-based nanoemulsions to enhance the stability, bioaccessibility and synergistic immune activity of astaxanthin - Le Cheng; Yuxi Ling; Xinyu Zhai; Haibin Ren; Yue Fan; Difeng Ren (Food Chemistry, 2026)

Multifunctional sericin/alginate hydrogel integrated with cerium oxide nanozyme for accelerating methicillin-resistant Staphylococcus aureus-infected wound healing - Haiyang Liu; Yingjie Shen; Xin Xie; Xudong Mao; Jin Ren; Cunming Peng; Liangliang Wang; Junbo Zhou; Le Zhang; Lulu Zhang; Changchun Peng; Haixia Ge; et al. (Chemical Engineering Journal, 2026)

Distinct dose-response patterns between methane production and oxidation to urea or (NH4)2SO4 input in Chinese paddy fields - Wang-ting Yang; Bing-jie Ren; Si-le Wen; Yi-zhu Zhu; Jiang-bing Xu; Li-dong Shen; Wei-qi Wang; Jordi Sardans; Josep Peñuelas (Applied Soil Ecology, 2026)

Self-assembled mixed-conductive interphase enables stable solid-state sodium batteries - Hengxiang Wang; Le Xiang; Yun Shen; Lurong Xia; Xiaodi Ren; Xiaowen Zhan; Lingyun Zhu (Chemical Engineering Journal, 2026)

Isolation, structural characteristics and cytotoxicity of the constitutes from Ceratocarpus arenarius L - Aimulaguli Kuerban; Jiangping Pu; Dongyu Lei; Huijuan Liu; Xingyu Ren; Lu Jin; Le Pan (Natural Product Research, 2026)

Treatment performance and mechanism of source-separated blackwater using an earthworm-based reactor for rural applications - Le Zhong; Guang-Feng Liu; Shi-Chao Liang; Jie Ding; Han-Jun Sun; Ding-Ding Tang; Yan Zhou; Xiong Qin; Ji-Wei Pang; Yan Li; Nan-Qi Ren; Shan-Shan Yang (Journal of Environmental Management, 2026)

Dual-species biofilm formation of Pseudomonas fluorescens and Hafnia alvei and their susceptibility to penicillin V acylase from Lactiplantibacillus plantarum YP4-1-2 - Wenqi Yang; Xiangrong Wang; Shuilin Liu; Le An; Anqi Ren; Xinran Lv; Jianrong Li; Xuepeng Li; Meihui Li (International Journal of Food Microbiology, 2026)

Radiofrequency-responsive liposomal hydrogels loaded 3-bromopyruvate energizes artery embolization on liver cancer - Chao Liu; Yanqiao Ren; Can Hong; Xuyu Li; Mengqing Guo; Le Zhao; Yan Liu; Chuansheng Zheng; Xiangliang Yang; Yanbing Zhao (Chemical Engineering Journal, 2026)

The presence of microplastics in human semen and the protective role of nicotinamide mononucleotide against polystyrene nanoplastics-induced reproductive and early embryonic toxicity - Fa Ren; Jingliang Pei; Le Li; Di Yuan; Fengdan Hao; Pengyun Qiao; Yingdong Liu (Journal of Hazardous Materials, 2026)

Brazide: A breakthrough plant growth regulator that delays leaf senescence under heat stress to promote grain yield in winter wheat (Triticum aestivum L.) - Xingyu Zhong; Qihua Wu; Le Yang; Ziqing Lin; Dan Ren; Zhaohu Li; Yuyi Zhou; Liusheng Duan (Field Crops Research, 2026)

Cytoskeletal control of development and environmental adaptation in plants - Yi Zhang; Jiejie Li; Yun Xiang; Pengwei Wang; Jie Le; Yanping Jing; Ting Wang; Xiangfeng Wang; Lei Zhu; Dong Qian; Guangda Wang; Peiwei Liu; et al. (Science China Life Sciences, 2026)

A Network Information-Based Behavior Change Wheel for Populations at High Risk of Developing Gastric Cancer - Wen-Lei Huang; Shi-Guang Ren; Le-Jian He; Fen Xie; Hui-Lan Zhai; Dan-Dan Wang; Lu Jiang; Xue-Qin Li (Journal of Cancer Education, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Macroclimate determines whether tree growth at alpine treelines is primarily limited by temperature or precipitation in northern China - Hanxue Liang; Jinji Li; Yimin Ren; Le Wang; Zhitao Wu (Dendrochronologia, 2026)

Coupled Dynamic Analysis of Offshore Wind Substation Hoisting Process Considering Variation of Hoisting Speed - Junqi Ren; Conghuan Le; Kai Wang; Puyang Zhang; Hongyan Ding (Journal of Ocean University of China, 2026)

Electrochemical ammonia recovery from wastewater: The critical roles of electrode engineering toward scale-up - Dejia Liu; Jixin Yuan; Panyu Ren; Le Shi; Zhiping Zhu; Changyong Zhang; Hongmin Dong; Dezhao Liu (Water Research, 2026)

Low-cholesterol egg yolk lipids alleviated the development of atherosclerosis in ApoE −/− mice by regulating bile acid metabolism and gut microbiota - Le Cheng; Ming Zhang; Fang Wu; Jianguo Dong; Yifei Wang; Lin Dong; Yumeng Ma; Chenyan Zheng; Zihan Wang; Yixuan Li; Ran Wang; Fazheng Ren; et al. (Food Research International, 2026)

Greenspace exposure and its dual role as mediator and moderator in the relationship between urban density and mental health - Liu Hongxiao; Pang Yujin; Jiao Min; Sun Xiao; Ren Hai; Luo Le; Han Taotao; Li Yuan; Zheng Shanwen; Sui Chunhua (Landscape and Urban Planning, 2025)

Thermotolerance and antiapoptosis enhancement by Lycium barbarum polysaccharide: counteracting mitochondrial oxidative stress in human sperm exposed to decabromodiphenyl ether (BDE-209) at 37 °C - Pengyun Qiao; Le Li; Zilong Li; Feifan Sun; Fa Ren (Journal of Thermal Biology, 2025)

Enhancing the degradation of ciprofloxacin and levofloxacin by peroxydisulfate (PDS): Multiple roles of co-existing copper ion - Kaixin Sun; Bo Gong; Chang Xu; Shan Zhao; Shuguang Wang; Le Ren; Chao Song (Journal of Environmental Chemical Engineering, 2025)

Ionospheric disturbances over the American sector during the May 2024 solar storm: flares and geomagnetic effects (May 9–15) - Ahmed Abdelaziz; Xiaodong Ren; Xuan Le; Chen Jinyuan; Dengkui Mei; Jinsheng Zhang; Xiaohong Zhang (Advances in Space Research, 2025)

Dose-response patterns of anaerobic oxidation of methane to nitrogen addition in Chinese paddy fields - Wang-ting Yang; Qi-nan Hu; Si-le Wen; Bing-jie Ren; Evgenios Agathokleous; Li-dong Shen; Wei-qi Wang (Soil Biology and Biochemistry, 2025)

Harnessing reactive manganese species for geosmin abatement in the permanganate/bisulfite process: From bench-scale to pilot-scale applications - Nan Li; Le Peng; Wei Ren; Zhijun Ouyang; Lingjun Bu; Yangtao Wu; Shiqing Zhou (Journal of Environmental Management, 2025)

“Framework Channel catalysis”: A multiphase synergistic Zn-based coating strategy for high-performance zinc-ion batteries - Yue Shi; Le Li; Chao Tan; Conghui Wang; Yuanyuan Yang; Haoyuan Du; Mengyao Guo; Xiaohu Yu; Zhigui Ren; Yongqiang Ji; Guotai Sun; Hengwei Qiu; et al. (Chemical Engineering Journal, 2025)

Lateral bearing characteristics of an innovative tetrapod bucket foundation for offshore wind turbines - Conghuan Le; Junqi Ren; Hanbo Zhai; Puyang Zhang; Hongyan Ding (Ocean Engineering, 2025)

Aging influence and long-term stable mechanism of biofuel ash immobilizing cadmium in alkaline soil combining artificial aging simulation - Le Song; Wengeng Cao; Yu Ren; Rong Zhang; Zhaoji Zhang; Jiazhong Qian (Environmental Research, 2025)

Effects of mineral admixtures on time-dependent behavior of high-strength self-compacting concrete-filled steel tubes - Huan-Chi Ma; Yue Geng; Ren-Le Bin; Guo-Dong Li; Yu-Yin Wang (Engineering Structures, 2025)

Population pharmacokinetics of levetiracetam in Chinese adult epilepsy patients with varying renal function: exposure simulation and individualized dosing adjustments - Rongrong Wang; Ze Li; Shu Li; Yaoyu Zhang; Le Cai; Tinglin Ren; Rongyan Li; Xingang Li; Tianlin Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Intelligent detection of traveling ionospheric disturbances from dense GNSS TEC observations utilizing instance segmentation model Cascade Mask R-CNN - Xiaodong Ren; Pengchong Zhao; Xuan Le; Linghuo Jian; Ahmed Abdelaziz; Xiaohong Zhang (GPS Solutions, 2025)

Associations between blood levels of persistent organic pollutants and oxidative stress biomarkers among women in France in the 90's - Pauline Frénoy; German Cano-Sancho; Jean-Philippe Antignac; Philippe Marchand; Bruno Le Bizec; Chloé Marques; Xuan Ren; Vittorio Perduca; Francesca Romana Mancini (Environmental Research, 2025)

Effects of polystyrene microplastics on growth, physiological traits of Microcystis aeruginosa and microcystin production and release - Xiaotao Zhou; Sifan Zhou; Xinyi Duan; Nan Zhang; Yujing Ren; Le Liang; Xiaoxin Ye (Environmental Pollution, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

The efficient separation of bioactive components from Eucommia ulmoides Oliver using membrane filtration technology and its mechanisms in preventing alcoholic liver disease - Xiao-Na Le; Da-Ping Long; Shuang-Shuang Yin; Ren-Yan Qing; Zhi-Zheng Chi; Ming-Qing Gao; Ming-Qiang Zhu (Carbohydrate Polymers, 2025)

Rapid detection of the phytopathogenic oomycete Phytopythium helicoides with a visualized loop-mediated isothermal amplification assay - Le-Yao Ren; Ke Wen; Bao-Ping Cheng; Jing‑Hao Jin; Vaibhav Srivastava; Xiao-Ren Chen (Brazilian Journal of Microbiology, 2025)

Ionospheric total electron content and electron density response induced by the 8 April 2024 total solar eclipse - Xuan Le; Dengkui Mei; Jinyuan Chen; Ahmed Abdelaziz; Xiaodong Ren; Xiaohong Zhang (Advances in Space Research, 2025)

Enhancing the carbon sequestration potential of urban green space: A water–energy–carbon fluxes perspective - Yilun Qu; Yan Shi; Xu Wu; Minghui Zhu; Pengfei Zhu; Xiao Zhang; Shuangying Le; Yuan Ren; Jianyun Pan; Yixiang Wang (Urban Forestry & Urban Greening, 2025)

Influence of precipitation and temperature variability on anthropogenic nutrient inputs in a river watershed: Implications for environmental management - Shuhui Zhang; Xia Li; Ze Ren; Cheng Zhang; Le Fang; Xiaobiao Mo; Wei Yang; Xinhui Liu (Journal of Environmental Management, 2025)

Positively charged mesoporous silica nanocarriers loaded with arbidol: A novel effective nano antiviral system against nervous necrosis virus - Xiang Liu; Zong-Yi Ren; Qin-Xue Liu; Jia-Le Zhou; Bin Yang; Peng-Fei Li; Tian-Qiang Liu; Fei Ling; Gao-Xue Wang (Aquaculture, 2025)

Surface chemistry regulation enables highly durable superhydrophobic coatings with environmental robustness and pH-triggered recoatability - Mei-Lin Guo; Fang Wang; Ren-Yi Sun; Chun-Bo Li; Jin-Le Li; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Comparative study on genesis mechanism of high arsenic groundwater in typical alluvial plain of the Upper and lower Yellow River, China - Jiju Guo; Wengeng Cao; Xiangzhi Li; Yu Ren; Chongsheng Lu; Yanyan Wang; Le Song; Yang Liu; Xiaoyue Sun (Science of The Total Environment, 2024)

Coupling dynamic characteristics of installation vessel - Multi buckets jacket foundation lowering system - Puyang Zhang; Jianyu Ren; Jinxin Cai; Conghuan Le; Hongyan Ding (Ocean Engineering, 2024)

Bioconversion of sugar beet molasses into functional exopolysaccharides by beet juice-derived lactic acid bacteria - Gaoyu Ren; Wentao Luo; Hao Gan; Han Zhang; Xiaoyan Hou; Shanshan Li; Anjun Chen; Zhiqing Zhang; Le Pan; Shuna Zhao; Guanghui Shen (Food Bioscience, 2024)

Does the digital economy promote environmental performance increase? Evidence from China 258 cities - Dong Le; Fei Ren; Yusong Li (Environment, Development and Sustainability, 2024)

Deciphering the roles of attached and suspended sludges in simultaneous nitrogen and phosphorus removal in an IFAS system based on metagenomic analysis - Tong Wu; Jie Ding; Han-Jun Sun; Ji-Wei Pang; Le Zhong; Lei Zhao; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Journal of Environmental Management, 2024)

Integrated induction of silver resistance determinants and production of extracellular polymeric substances in Cupriavidus metallidurans BS1 in response to silver ions and silver nanoparticles - Jia-Xin Dai; Yanshuang Yu; Le-Xing You; Hong-Lin Zhong; Yuan-Ping Li; Ai-Jun Wang; Jon Chorover; Ren-Wei Feng; Hend A. Alwathnani; Martin Herzberg; Christopher Rensing (Chemosphere, 2024)

Stronger influences of grassland growth than grassland area on hydrological processes in the source region of the Yellow River - Hao Zhan; Dongxue Yu; Le Wang; Jiang Zhang; Min Xu; Xiuqin Fang; Kai Xue; Yiqi Yan; Liliang Ren; Yanfen Wang; Qiuan Zhu (Journal of Hydrology, 2024)

Inhibition effect of marine active peptides SF on dual-species biofilms of Vibrio parahaemolyticus and Aeromonas sobria - Xinran Lv; Wenqi Yang; Shuilin Liu; Xueqing Liu; Shuo Yuan; Le An; Anqi Ren; Fengling Bai; Jianrong Li; Xuepeng Li; Yuqiong Meng; Rui Ma (Food Bioscience, 2024)

Insight into effect of polyethylene microplastic on nitrogen removal in moving bed biofilm reactor: Focusing on microbial community and species interactions - Tong Wu; Jie Ding; Sheng Wang; Ji-Wei Pang; Han-Jun Sun; Le Zhong; Nan-Qi Ren; Shan-Shan Yang (Science of The Total Environment, 2024)

Ciprofloxacin affects nutrient removal in manganese ore-based constructed wetlands: Adaptive responses of macrophytes and microbes - Le Zhong; Han-Jun Sun; Ji-Wei Pang; Jie Ding; Lei Zhao; Wei Xu; Fang Yuan; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Journal of Hazardous Materials, 2024)

New insights into substrates shaped nutrients removal, species interactions and community assembly mechanisms in tidal flow constructed wetlands treating low carbon-to-nitrogen rural wastewater - Le Zhong; Shan-Shan Yang; Han-Jun Sun; Chen-Hao Cui; Tong Wu; Ji-Wei Pang; Lu-Yan Zhang; Nan-Qi Ren; Jie Ding (Water Research, 2024)

Identification critical host factors for Japanese encephalitis virus replication via CRISPR screening of human sgRNA library - Le-le Liu; You-qin Yin; Kai-xiong Ma; Jin-chao Xing; Xing-xing Ren; Jin-yu Huang; Ming Liao; Wen-bao Qi; Li-hong Huang (Veterinary Microbiology, 2024)

Microplastics shaped performance, microbial ecology and community assembly in simultaneous nitrification, denitrification and phosphorus removal process - Tong Wu; Jie Ding; Ying-Jun Zhao; Lan Ding; Yani Zang; Han-Jun Sun; Le Zhong; Ji-Wei Pang; Yan Li; Nan-Qi Ren; Shan-Shan Yang (Science of The Total Environment, 2024)

Preparation and characterization of polyethylene-based composite films coated with carboxymethyl chitosan/sodium alginate/nisin and application in the packaging of Rosa roxburghii Tratt - Le Cheng; Xue Li; Siyang An; Zihan Liu; Yuanyuan Liu; Difeng Ren (Food Packaging and Shelf Life, 2024)

High-Stress Chamber Stability in Kilometer-Deep Coal Mines: A Case Study - Jin-xiao Liu; Yi-ning Zheng; Ren-Bao Zhao; Sheng-shi Meng; Yong-le Liu; Chang Sun (Geotechnical and Geological Engineering, 2024)

Geochemical relationships between shells of the gastropod Gyraulus convexiusculus and modern water bodies on the Tibetan Plateau, and their paleoenvironmental significance - Feng Chen; Jiao-Yan Zhao; Jiao Ren; Jin-Liang Feng; Hai-Ping Hu; Feng-Mei Ban; Le-Le Pei; Yu-Zhi Zhang; Kun-Ying Wang (Quaternary Science Reviews, 2024)

Rolling forms the diversities of small molecular nonvolatile metabolite profile and consequently shapes the bacterial community structure for Keemun black tea - Zhi-Wei Ren; Hong-Jing Pan; Cheng Hu; Miao-Miao Le; Yan-Hua Long; Qian Xu; Zhong-Wen Xie; Tie-Jun Ling (Food Research International, 2024)

Research on anchoring force of the deep-sea stratum drilling robot - Peihao Zhang; Jiawang Chen; Yongqiang Ge; Xingshuang Lin; Xiaoling Le; Zixin Weng; Ziqiang Ren (Marine Georesources & Geotechnology, 2024)

Functionally responsive hydrogels with salt-alkali sensitivity effectively target soil amelioration - Le Qi; Xiao Xiao; Ting Liu; Zhong Ren; Wei Ren; Qifeng Gao; Mengting Liu; Pangzhi Wei; Yongkang Lai; Weipeng Yao; Huanhuan An; Lan Zhang; et al. (Science of The Total Environment, 2024)

The impact of dynamic traffic and wind conditions on green infrastructure performance to improve local air quality - Meng-Yi Jin; Le-Ying Zhang; Zhong-Ren Peng; Hong-Di He; Prashant Kumar; John Gallagher (Science of The Total Environment, 2024)

A top-down and in situ strategy for intrinsic acicular nanostructure enhanced ultradurable superhydrophobic and anti-icing aramid fabric - Jin-Le Li; Fang Wang; Chun-Bo Li; Ren-Yi Sun; Mei-Lin Guo; Gang Wu; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

A study on wildfire impacts on greenhouse gas emissions and regional air quality in South of Orléans, France - Chaoyang Xue; Gisèle Krysztofiak; Yangang Ren; Min Cai; Patrick Mercier; Frédéric Le Fur; Corinne Robin; Benoit Grosselin; Véronique Daële; Max R. McGillen; Yujing Mu; Valéry Catoire; et al. (Journal of Environmental Sciences, 2024)

IROTI: a new index to detect and identify traveling ionospheric disturbances and equatorial plasma bubbles - Xiaodong Ren; Xuan Le; Dengkui Mei; Hang Liu; Xiaohong Zhang (GPS Solutions, 2024)

Influence of subducted carbonate on the composition of basalts in the Paleo-Asian Ocean domain - Sheng-Peng Wang; Jie Li; Zhong-Yuan Ren; Tserendash Narantsetseg; Qing-Lin Zhang; Qiao-Hui Zhong; Le Zhang; Chao Yuan (Gondwana Research, 2023)

Correction: Anti-Inflammatory Mechanism of Walnut Meal Peptide/ Ellagic Acid Nanoparticles on LPS-Stimulated RAW264.7 Cells by Inhibition of NFκB and MAPK Activation - Yuxi Ling; Yanxia Feng; Ziqi Li; Le Cheng; Xuan Zhang; Difeng Ren (International Journal of Peptide Research and Therapeutics, 2023)

Cenozoic mantle plume activity in East Asia: Constraints from geochemistry of olivine, spinel, and melt inclusions - Sheng-Peng Wang; Zhong-Yuan Ren; Alexander R.L. Nichols; Tserendash Narantsetseg; Qing-Lin Zhang; Le Zhang; Chao Yuan (Lithos, 2023)

The resource utilization of coal gasification wastewater by co-slurry with lignite: Slurryability, dispersion/aggregation behavior, and co-slurrying mechanisms - Suqian Gu; Zhiqiang Xu; Yunxiang Dai; Yang Chen; Yangguang Ren; Yanan Tu; Le Yang; Mengyun Shi (Fuel, 2023)

Targeted control of soil erosion through selective regulation of Eleocharis yokoscensis using mixed endophytes - Qifeng Gao; Xiao Xiao; Ting Liu; Zhong Ren; Wei Ren; Yunya Zhan; Wenqian Wang; Weiran Feng; Li Ma; Le Qi; Zixian Zhang; Xubiao Luo; et al. (CATENA, 2023)

Anti-Inflammatory Mechanism of Walnut Meal Peptide/ Ellagic Acid Nanoparticles on LPS-Stimulated RAW264.7 Cells by Inhibition of NF-κB and MAPK Activation - Yuxi Ling; Yanxia Feng; Ziqi Li; Le Cheng; Xuan Zhang; Difeng Ren (International Journal of Peptide Research and Therapeutics, 2023)

FARM: A fully automated rice mapping framework combining Sentinel-1 SAR and Sentinel-2 multi-temporal imagery - Yuan Gao; Yaozhong Pan; Xiufang Zhu; Le Li; Shoujia Ren; Chuanwu Zhao; Xuechang Zheng (Computers and Electronics in Agriculture, 2023)

Sulfate-reducing ammonium oxidation: A promising novel process for nitrogen and sulfur removal - Tong Wu; Jie Ding; Le Zhong; Han-Jun Sun; Ji-Wei Pang; Lei Zhao; Shun-Wen Bai; Nan-Qi Ren; Shan-Shan Yang (Science of The Total Environment, 2023)

Experimental research on the lowering process of the three and four-bucket jacket foundation of offshore wind turbine - Puyang Zhang; Jianyu Ren; Yan'e Li; Conghuan Le; Hongyan Ding (Ocean Engineering, 2023)

Mechanistic insight into the adsorption and interaction of lignite, organic ingredients, and dispersant in coal wastewater slurry - Suqian Gu; Zhiqiang Xu; Le Yang; Yujia Wang; Yangguang Ren; Yunxiang Dai; Yanan Tu (Journal of Environmental Chemical Engineering, 2023)

Microplastics perturb nitrogen removal, microbial community and metabolism mechanism in biofilm system - Tong Wu; Le Zhong; Jie Ding; Ji-Wei Pang; Han-Jun Sun; Meng-Qi Ding; Nan-Qi Ren; Shan-Shan Yang (Journal of Hazardous Materials, 2023)

High-yield preparation of coal tar pitch based porous carbon via low melting point fire retardant carbonation strategy for supercapacitor - Fuhe Le; Pengxu Ren; Wei Jia; Tao Wang; Yuan Tao; Dongling Wu (Chemical Engineering Journal, 2023)

Study on the influence of key active groups on gas products in spontaneous combustion of coal - Teng Ma; Xiao-Wei Zhai; Yang Xiao; Ya-E Bai; Kun Shen; Bo-Bo Song; Le Hao; Li-Feng Ren; Xiao-Kun Chen (Fuel, 2023)

Large-deformation modelling of earthquake-triggered landslides considering non-uniform soils with a stratigraphic dip - Shun-Ping Ren; Xue-Jian Chen; Zeng-Le Ren; Po Cheng; Yong Liu (Computers and Geotechnics, 2023)

Grazing reduces plant sexual reproduction but increases asexual reproduction: A global meta-analysis - Mi Wentao; Tang Shiming; Qi Le; Ren Weibo; Ellen L. Fry; Jonathan R. De Long; Reuben C.P. Margerison; Chi Yuan; Liu Xiaomin (Science of The Total Environment, 2023)

Darriwilian–Sandbian (Middle–Late Ordovician) shallow warm-water deposits in the Upper Yangtze region, South China: A case study from the Qiaojia area, northeastern Yunnan Province - Xiao-Cong Luan; Xiao-Le Zhang; Qi-Jian Li; Yong Wang; Yu-Nong Cui; Ren-Bin Zhan (Palaeoworld, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

Recent advances towards micro(nano)plastics research in wetland ecosystems: A systematic review on sources, removal, and ecological impacts - Le Zhong; Tong Wu; Han-Jun Sun; Jie Ding; Ji-Wei Pang; Luyan Zhang; Nan-Qi Ren; Shan-Shan Yang (Journal of Hazardous Materials, 2023)

Genome-wide Transcriptome Analysis Reveals the Gene Regulatory Network in Star Fruit Flower Blooming - Si Qin; Xiao-Ping Li; Chun-Mei Wu; Le You; Donghui Peng; Sagheer Ahmad; Hui Ren; Zhong-Jian Liu; Jun-Wen Zhai; Sha-Sha Wu (Tropical Plant Biology, 2023)

Highly Efficient Utilization of Sugar in Molasses for Butyric Acid Production by Clostridium tyrobutyricum - Bing Wang; Xiang Zhou; Jun-Le Ren; Miao-Miao Zhang; Qing-Feng Wu; Shan Yuan; Wei Liu; Dong Lu (Sugar Tech, 2023)

Reversal of H2O2-induced cell death by knockdown of HOTAIR in HTR-8/SVneo cells by mediation of miR-106b-5p/ACSL4 axis - Minkai Cao; Weilai Jin; Ying Li; Mingxin Wang; Faguang Wan; Yongwei Ren; Ying Gu; Jinqi Ma; Le Zhang (Functional & Integrative Genomics, 2023)

Synergistic analysis of performance, functional genes, and microbial community assembly in SNDPR process under Zn(II) stress - Tong Wu; Jie Ding; Le Zhong; Yi-Lin Zhao; Han-Jun Sun; Ji-Wei Pang; Lei Zhao; Shun-Wen Bai; Nan-Qi Ren; Shan-Shan Yang (Environmental Research, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

An Anterior Cingulate Cortex-to-Midbrain Projection Controls Chronic Itch in Mice - Ting-Ting Zhang; Su-Shan Guo; Hui-Ying Wang; Qi Jing; Xin Yi; Zi-Han Hu; Xin-Ren Yu; Tian-Le Xu; Ming-Gang Liu; Xuan Zhao (Neuroscience Bulletin, 2023)
Itch is an unpleasant sensation that provokes the desire to scratch. While acute itch serves as a protective system to warn the body of external irritating agents, chronic itch is a debilitating but poorly-treated clinical disease leading to repetitive scratching and skin lesions. However, the neural mechanisms underlying the pathophysiology of chronic itch remain mysterious. Here, we identified a cell type-dependent role of the anterior cingulate cortex (ACC) in controlling chronic itch-related excessive scratching behaviors in mice. Moreover, we delineated a neural circuit originating from excitatory neurons of the ACC to the ventral tegmental area (VTA) that was critically involved in chronic itch. Furthermore, we demonstrate that the ACC→VTA circuit also selectively modulated histaminergic acute itch. Finally, the ACC neurons were shown to predominantly innervate the non-dopaminergic neurons of the VTA. Taken together, our findings uncover a cortex–midbrain circuit for chronic itch-evoked scratching behaviors and shed novel insights on therapeutic intervention.

Mechanical properties of auxetic circular and square tubes filled with aluminum foam - Ru Yuan Huo; Dong Han; Yi Zhang; Wei Jiang; Le Yang Fan; Xin Wei Peng; Ge Chen Jie Shi; Ming Hao Chu; Xiang Yu Zhang; Yi Min Xie; Xin Ren (Engineering Structures, 2023)

Jumping of flea beetles onto inclined platforms - Le Zong; Jianing Wu; Pingping Yang; Jing Ren; Guanya Shi; Siqin Ge; David L. Hu (Journal of Comparative Physiology A, 2023)

Hydrodynamic loads of the bridge decks in wave-current combined flows - Le-Em Huynh; Chia-Ren Chu; Tso-Ren Wu (Ocean Engineering, 2023)

Mantle source heterogeneity for Hainan basalts revealed by Pb and Sr isotopic compositions in olivine-hosted melt inclusions - Qi-Wei Hu; Sheng-Wang Mei; Le Zhang; Zhong-Yuan Ren (Lithos, 2023)

Bibliometric overview of research progress, challenges, and prospects of rural domestic sewage: Treatment techniques, resource recovery, and ecological risk - Le Zhong; Jie Ding; Tong Wu; Yi-lin Zhao; Ji Wei Pang; Ji-Ping Jiang; Jun-Qiu Jiang; Yan Li; Nan-Qi Ren; Shan-Shan Yang (Journal of Water Process Engineering, 2023)

AcHKT1;2 is a candidate transporter mediating the influx of Na+ into the salt bladder of Atriplex canescens - Huan Guo; Yan-Nong Cui; Le Zhang; Shan Feng; Zhi-Jie Ren; Suo-Min Wang; Ai-Ke Bao (Plant and Soil, 2023)

The star target in SLE: IL-17 - Yi Yang; Chen Yan; Le Yu; Xiuling Zhang; Jingjing Shang; Jie Fan; Rongwei Zhang; Jie Ren; Xinwang Duan (Inflammation Research, 2023)

Mapping urban morphology changes in the last two decades based on local climate zone scheme: A case study of three major urban agglomerations in China - Jiyao Zhao; Guangzhao Chen; Le Yu; Chao Ren; Jing Xie; Lamuel Chung; Hao Ni; Peng Gong (Urban Climate, 2023)

Co-composting of faecal sludge and carbon-rich wastes in the earthworm's synergistic cooperation system: Performance, global warming potential and key microbiome - Le Zhong; Tong Wu; Jie Ding; Wei Xu; Fang Yuan; Bing-Feng Liu; Lei Zhao; Yan Li; Nan-Qi Ren; Shan-Shan Yang (Science of The Total Environment, 2023)

Simultaneous nitrification, denitrification and phosphorus removal: What have we done so far and how do we need to do in the future? - Tong Wu; Shan-Shan Yang; Le Zhong; Ji-Wei Pang; Luyan Zhang; Xue-Fen Xia; Fan Yang; Guo-Jun Xie; Bing-Feng Liu; Nan-Qi Ren; Jie Ding (Science of The Total Environment, 2023)

Discrimination of the harvesting season of green tea by alcohol/salt-based aqueous two-phase systems combined with chemometric analysis - Xiao-Hua Zhang; Hui-Na Cui; Jing-Jing Zheng; Xiang-Dong Qing; Kai-Long Yang; Ya-Qian Zhang; Lu-Meng Ren; Le-Yuan Pan; Xiao-Li Yin (Food Research International, 2023)

Multifunctional, breathable MXene-PU mesh electronic skin for wearable intelligent 12-lead ECG monitoring system - Tianrui Cui; Yancong Qiao; Ding Li; Xiaorui Huang; Le Yang; Anzhi Yan; Zhikang Chen; Jiandong Xu; Xichao Tan; Jinming Jian; Zhen Li; Shourui Ji; et al. (Chemical Engineering Journal, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Olivine and melt inclusion chemical constraints on the nature and origin of the common mantle component beneath eastern Asia - Jian-Qiang Liu; Li-Hui Chen; Xiao-Jun Wang; Hui-Li Zhang; Gang Zeng; Saskia Erdmann; Le Zhang; Zhong-Yuan Ren (Contributions to Mineralogy and Petrology, 2022)

Retraction Note to: Sustained Delivery of Timolol Using Nanostructured Lipid Carriers-Laden Soft Contact Lenses - Chenfei Tian; Lu Zeng; Le Tang; Jingni Yu; Mei Ren (AAPS PharmSciTech, 2022)

Expression of matrix metalloproteinases and tissue inhibitors of metalloproteinases in the hippocampus of lithium-pilocarpine-induced acute epileptic rats - Ding Wan; Lu Yang; Jia Ren; Haiyue Huang; Chen Zhang; Le Chen; Xueyao Su; Qi Huang; Jianguo Niu; Tao Sun; Peng Wang (Molecular Biology Reports, 2022)

Viridibacillus soli sp. nov., isolated from forest soil in Ailaoshan National Nature Reserve - Yan Xu; Jiang-Yuan Zhao; Yu Geng; Hui-Ren Yuan; Le-Le Li; Meng-Liang Wen; Ming-Gang Li; Shu-Kun Tang (Archives of Microbiology, 2022)

Propioniciclava soli sp. nov., isolated from forest soil, Yunnan, China, and reclassification of the genus Brevilactibacter into the genus Propioniciclava, and Brevilactibacter sinopodophylli, Brevilactibacter flavus, and Brevilactibacter coleopterorum as Propioniciclava sinopodophylli comb. nov., Propioniciclava flava comb. nov., and Propioniciclava coleopterorum comb. nov., respectively - Le-Le Li; Jiang-Yuan Zhao; Yu Geng; Yu-Guang Zhou; Hui-Ren Yuan; Man Cai; Meng-Liang Wen; Ming-Gang Li; Shu-Kun Tang (Archives of Microbiology, 2022)

Estrogen prevents cellular senescence and bone loss through Usp10-dependent p53 degradation in osteocytes and osteoblasts: the role of estrogen in bone cell senescence - Yu Wei; Jiayao Fu; Wenjing Wu; Pengfei Ma; Le Ren; Junhua Wu (Cell and Tissue Research, 2021)

Food-grade γ-aminobutyric acid production by immobilized glutamate decarboxylase from Lactobacillus plantarum in rice vinegar and monosodium glutamate system - Li-Li Yao; Jia-Ren Cao; Chang-Jiang Lyu; Fang-Fang Fan; Hong-Peng Wang; Hong-Wei Cao; Jun Huang; Le-He Mei (Biotechnology Letters, 2021)

RETRACTED ARTICLE: Sustained Delivery of Timolol Using Nanostructured Lipid Carriers-Laden Soft Contact Lenses - Chenfei Tian; Lu Zeng; Le Tang; Jingni Yu; Mei Ren (AAPS PharmSciTech, 2021)

Aestuariimicrobium ganziense sp. nov., a new Gram-positive bacterium isolated from soil in the Ganzi Tibetan autonomous prefecture, China - Yu Geng; Jiang-Yuan Zhao; Hui-Ren Yuan; Le-Le Li; Meng-Liang Wen; Ming-Gang Li; Shu-Kun Tang (Archives of Microbiology, 2021)

Towing Performance of the Submerged Floating Offshore Wind Turbine under Different Wave Conditions - Conghuan Le; Jianyu Ren; Kai Wang; Puyang Zhang; Hongyan Ding (Journal of Marine Science and Engineering, 2021)
One of the advantages of floating offshore wind turbines (FOWTs) is that they can be designed to be easily wet towed and installed to reduce the cost of offshore construction. In this paper, a fully coupled towing system numerical model is established for a novel 10 MW FOWT concept, namely, a submerged floating offshore wind turbine (SFOWT) to investigate the towing performance. Firstly, the numerical simulation is validated by comparison with model experiment results. Then, a series of numerical simulations are conducted to predict and compare the towing performance for a three-column SFOWT (TC-SFOWT) and a four-column SFOWT (FC-SFOWT) under different wave conditions. The results show that the two forms of SFOWT have good towing performance when the significant wave height is less than 5 m, which is the maximum wave height for the allowable towing condition. The FC-SFOWT shows relatively better performance in heave motion and roll motion, but the towing force is relatively larger compared with the TC-SFOWT under the same condition. When the significant wave height is 5 m, the maximum values of heave motion, pitch motion, and roll motion of the TC-SFOWT are 2.51 m, 2.14°, and 1.38°, respectively, while they are 2.25 m, 2.70°, and 1.21°, respectively, for the FC-SFOWT. Both the roll motion and the pitch motion are satisfied with the requirement that the roll and pitch are less than 5° during the towing process. The mean towing force of FC-SFOWT is 159.1 t at the significant wave height of 5 m, which is 52.8% larger than that of TC-SFOWT. The peak period mainly influences the frequency where the response peak appears in power spectra. The findings in this paper could provide some guidelines for wet towed operations.

Meta-analysis of the effect of the overexpression of aquaporin family genes on the drought stress response - Jianhong Ren; Xiaoxiao Yang; Chunying Ma; Yuling Wang; Juan Zhao; Le Kang (Plant Biotechnology Reports, 2021)

Exploring difference in land surface temperature between the city centres and urban expansion areas of China’s major cities - Jiyao Zhao; Le Yu; Yidi Xu; Xuecao Li; Yuyu Zhou; Dailiang Peng; Han Liu; Xiaomeng Huang; Zheng Zhou; Dong Wang; Chao Ren; Peng Gong (International Journal of Remote Sensing, 2020)

Comparison of Plasma Concentrations of Mercury, Cadmium, and Arsenic among Women in 2005 and 2012 in a Historically Contaminated Area in China - Lei Jin; Jing-ru Yu; Le Zhang; Ai-guo Ren (Biological Trace Element Research, 2020)

Prediction and Identification of Epitopes in the Emy162 Antigen of Echinococcus multilocularis - Ming-Quan Pang; Feng Tang; Hai-Jiu Wang; Ying Zhou; Li Ren; Run-Le Li; Hu Zhou; Chen-Fei Wan; Chuan-Chuan Liu; Cai-Rang Yangdan; Hai-Ning Fan (Acta Parasitologica, 2020)

Alternative complement pathway is activated in the brains of scrapie-infected rodents - Cao Chen; Yan Lv; Chao Hu; Xiao-Feng Xu; Ren-Qing Zhang; Kang Xiao; Yue Ma; Li-Ping Gao; Jian-Le Li; Qiang Shi; Jing Wang; Qi Shi; et al. (Medical Microbiology and Immunology, 2020)

Genome sequence analysis of Vibrio parahaemolyticus lytic phage Vp_R1 with a C3 morphotype - Hongyu Ren; Zhen Li; Le Xu; Xiaoyu Li; Lili Wang; Yongping Xu (Archives of Virology, 2019)

Exploring the addition of Landsat 8 thermal band in land-cover mapping - Jiyao Zhao; Le Yu; Yidi Xu; Huazhong Ren; Xiaomeng Huang; Peng Gong (International Journal of Remote Sensing, 2019)

On filtering ionospheric effects in GPS observations using the Matérn covariance family and its impact on orbit determination of Swarm satellites - Gaël Kermarrec; Le Ren; Steffen Schön (GPS Solutions, 2018)

Prevalence and trend of isolated and complicated congenital hydrocephalus and preventive effect of folic acid in northern China, 2005–2015 - Jufen Liu; Lei Jin; Zhiwen Li; Yali Zhang; Le Zhang; Linlin Wang; Aiguo Ren (Metabolic Brain Disease, 2018)

Hybrid absorbing boundary condition for three-dimensional elastic wave modeling - Xin Liu; Yang Liu; Zhi-Ming Ren; Xiao-Hui Cai; Bei Li; Shi-Gang Xu; Le-Kai Zhou (Applied Geophysics, 2017)

Toxicity and accumulation of zinc pyrithione in the liver and kidneys of Carassius auratus gibelio: association with P-glycoprotein expression - Tao Ren; Gui-Hong Fu; Teng-Fei Liu; Kun Hu; Hao-Ran Li; Wen-Hong Fang; Xian-Le Yang (Fish Physiology and Biochemistry, 2017)

Phytotoxicity mechanisms of two coumarin allelochemicals from Stellera chamaejasme in lettuce seedlings - Zhiqiang Yan; Dandan Wang; Haiyan Cui; Denghong Zhang; Yuhe Sun; Hui Jin; Xiuzhuang Li; Xiaoyan Yang; Hongru Guo; Xiaofeng He; Le Pan; Xia Ren; et al. (Acta Physiologiae Plantarum, 2016)

Neuropeptide S ameliorates olfactory spatial memory impairment induced by scopolamine and MK801 through activation of cognate receptor-expressing neurons in the subiculum complex - Yu-Feng Shao; Can Wang; Jun-Fan Xie; Xiang-Pan Kong; Le Xin; Chao-Yu Dong; Jing Li; Wen-Ting Ren; Yi-Ping Hou (Brain Structure and Function, 2016)

Mycophenolate mofetil plus prednisone for inducing remission of Henoch-Schönlein purpura nephritis: a retrospective study - Fei Han; Liang-liang Chen; Ping-ping Ren; Jing-yun Le; Pei-jing Choong; Hong-ju Wang; Ying Xu; Jiang-hua Chen (Journal of Zhejiang University-SCIENCE B, 2015)

In vitro study of the growth, development and pathogenicity responses of Fusarium oxysporum to phthalic acid, an autotoxin from Lanzhou lily - Zhijiang Wu; Liu Yang; Ruoyu Wang; Yubao Zhang; Qianhan Shang; Le Wang; Qin Ren; Zhongkui Xie (World Journal of Microbiology and Biotechnology, 2015)

Characterization of Soybean mosaic virus resistance derived from inverted repeat-SMV-HC-Pro genes in multiple soybean cultivars - Le Gao; Xueni Ding; Kai Li; Wenlin Liao; Yongkun Zhong; Rui Ren; Zhitao Liu; Karthikeyan Adhimoolam; Haijian Zhi (Theoretical and Applied Genetics, 2015)

Isolation and full-genome sequence of two reticuloendotheliosis virus strains from mixed infections with Marek’s disease virus in China - Ke-yan Bao; Yan-ping Zhang; Hui-wen Zheng; Hong-chao Lv; Yu-long Gao; Jing-fei Wang; Hong-lei Gao; Xiao-le Qi; Hong-yu Cui; Yong-qiang Wang; Xian-gang Ren; Xiao-mei Wang; et al. (Virus Genes, 2015)

Erratum to: Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

A novel missense mutation in collagenous domain of EDA gene in a Chinese family with X-linked hypohidrotic ectodermal dysplasia - DAXU LI; RAN XU; FUMENG HUANG; BIYUAN WANG; YU TAO; ZIJIAN JIANG; HAIRUI LI; JIANFENG YAO; PENG XU; XIAOKANG WU; LE REN; RUI ZHANG; et al. (Journal of Genetics, 2015)

Paternal epigenetic effects of population density on locust phase‐related characteristics associated with heat‐shock protein expression - Bing Chen; Shaoqin Li; Qiang Ren; Xiwen Tong; Xia Zhang; Le Kang (Molecular Ecology, 2015)
Many species exhibit transgenerational plasticity by which environmental cues experienced by either parent can be transmitted to their offspring, resulting in phenotypic variants in offspring to match ancestral environments. However, the manner by which paternal experiences affect offspring plasticity through epigenetic inheritance in animals generally remains unclear. In this study, we examined the transgenerational effects of population density on phase‐related traits in the migratory locust L ocusta migratoria . Using an experimental design that explicitly controls genetic background, we found that the effects of crowd or isolation rearing on phase plasticity could be inherited to the offspring. The isolation of gregarious locusts resulted in reduced weight in offspring eggs and altered morphometric traits in hatchlings, whereas crowding of solitarious locusts exhibited opposite effects. The consequences of density changes were transmitted by both maternal and paternal inheritance, although the expression of paternal effects was not as pronounced as that of maternal effects. Prominent expression of heat‐shock proteins ( Hsp s), such as Hsp90 , Hsp70 and Hsp20.6 , could be triggered by density changes. Hsp s were significantly upregulated upon crowding but downregulated upon isolation. The variation in parental Hsp expression was also transmitted to the offspring, in which the pattern of inheritance was consistent with that of phase characteristics. These results revealed a paternal effect on phase polyphenism and Hsp expression induced by population density, and defined a model system that could be used to study the paternal epigenetic inheritance of environmental changes.

Hyperacetylation of Histone H3K9 Involved in the Promotion of Abnormally High Transcription of the gdnf Gene in Glioma Cells - Zheng-Quan Yu; Bao-Le Zhang; Hai-Bo Ni; Ze-Hao Liu; Jian-Cun Wang; Qing-Xian Ren; Jian-Bing Mo; Ye Xiong; Rui-Qin Yao; Dian-Shuai Gao (Molecular Neurobiology, 2014)

BRG1 variant rs1122608 on chromosome 19p13.2 confers protection against stroke and regulates expression of pre-mRNA-splicing factor SFRS3 - Xin Xiong; Chengqi Xu; Yuting Zhang; Xiuchun Li; Binbin Wang; Fan Wang; Qin Yang; Dan Wang; Xiaojing Wang; Sisi Li; Shanshan Chen; Yuanyuan Zhao; et al. (Human Genetics, 2014)

Changes in Transcriptional Factor Binding Capacity Resulting from Promoter Region Methylation Induce Aberrantly High GDNF Expression in Human Glioma - Zheng-Quan Yu; Bao-Le Zhang; Qing-Xian Ren; Jian-Cun Wang; Ru-Tong Yu; De-Wei Qu; Ze-Hao Liu; Ye Xiong; Dian-Shuai Gao (Molecular Neurobiology, 2013)

The temporal changes in road stormwater runoff quality and the implications to first flush control in Chongqing, China - Qianqian Zhang; Xiaoke Wang; Peiqiang Hou; Wuxing Wan; Yufen Ren; Zhiyun Ouyang; Le Yang (Environmental Monitoring and Assessment, 2013)

Attachment of Acidithiobacillus ferrooxidans onto different solid substrates and fitting through Langmuir and Freundlich equations - Le-Xian Xia; Zhen Shen; Tomas Vargas; Wen-Juan Sun; Ren-Man Ruan; Zhen-Da Xie; Guan-Zhou Qiu (Biotechnology Letters, 2013)

Hydrogen sulfide enhances alfalfa (Medicago sativa) tolerance against salinity during seed germination by nitric oxide pathway - Yanqin Wang; Le Li; Weiti Cui; Sheng Xu; Wenbiao Shen; Ren Wang (Plant and Soil, 2012)

Shiga toxin type 2 (Stx2), a potential agent of bioterrorism, has a short distribution and a long elimination half-life, and induces kidney and thymus lesions in rats - Yue-Nan Liu; Sheng-han Wang; Tao Li; Qin Wang; Wei Tu; Kun Cai; Xiao-Jun Hou; Ren-Mao Tian; Xiang Gao; Hao Liu; Le Xiao; Jing Shi; et al. (Archives of Toxicology, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)